Design of Automatic Soup Filling Machine - Ruangraksa, Chanintorn; Sanposh, Peerayot (Srinakharinwirot University Engineering Journal, 2023)
The purpose of this project study was to design an automatic soup-filling machine. Due to the company's policy to increase production of efficiency, and maintain standards in producing products, and reduce the staff to fill the soup to automate the production line. Therefore, machines are designed based on existing and innovative technologies to operate automatically and efficiently without affecting the product and production process. The standard value of water content is 250 g/cup. The Shabu Soup Filling Machine, with six filling nozzles, can be filled automatically and accurately. It was found that the weight was within the value of the specified standard. After starting to use the soup-filling machine, it was able to reduce the cost of the soup-filling process costs 316,800 baht/year, and increase the efficiency of production from 1,200 cups/hour to 2,150 cups/hour, or 79.16 percent. The cost of this Shabu Soup Filling Machine is 200,000 Baht.